Morphological and RAPD Analysis of Fusarium Species Associated with Root and Stem Rot of Dendrobium Orchid in Northern Peninsula Malaysia - LATIFFAH ZAKARIA; NUR HAYATI M.D. ZAIN; BAHARUDDIN SALLEH; MAZIAH ZAKARIA (HAYATI Journal of Biosciences, 2009)
A total of 29 Fusarium isolates were isolated from Dendrobium orchid showing symptoms of root and stem rots. Based on morphological characteristics, three species were identified namely, F. oxysporum, F. solani, and F. proliferatum which were recovered from root and stem rots of Dendrobium. Cluster analysis of RAPD bands clearly separated F. oxysporum, F. proliferatum, and F. solani into distinct clusters. The present studies showed that three Fusarium species were isolated from root and stem rot of Dendrobium and cluster analysis of RAPD bands was in agreement with morphological characterization of the Fusarium species from root and stem rot of Dendrobium. Key words: orchid, Fusarium, root rot, stem rot, RAPD